2014
DOI: 10.7862/rm.2014.13
|View full text |Cite
|
Sign up to set email alerts
|

Fin-tube heat exchanger performance for different louver angles

Abstract: To choose the proper design for a heat exchanger in engineering industry and to evaluate the finned surface performance it is important to calculate fin efficiency. The heat transfer conditions, in tube-fin heat exchangers, can be modified for instance by changing the fin shapes. The angle of louver inclination affects the fluid flow direction and it has the effect on the heat transfer and temperature changes. In the paper, the heat transfer is estimated numerically for fins with and without louvers to choose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…More recently, Duan et al [24] revealed that longitudinal and transversal vortices can be created by using intermittent wavy fins with the flat tube HE and producing great heat transfer enhancement. P. Wais [25] performed a three-dimensional simulation using ANSYS software with fixed inlet air velocity and fin spacing to analyse the effect of louver inclination angle of a car radiator having circular tubes. They found that heat transfer depends strongly on the louver angle and the maximum value of the outlet air temperature reaches at 45º.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Duan et al [24] revealed that longitudinal and transversal vortices can be created by using intermittent wavy fins with the flat tube HE and producing great heat transfer enhancement. P. Wais [25] performed a three-dimensional simulation using ANSYS software with fixed inlet air velocity and fin spacing to analyse the effect of louver inclination angle of a car radiator having circular tubes. They found that heat transfer depends strongly on the louver angle and the maximum value of the outlet air temperature reaches at 45º.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, J. Dong et al [27] experimentally investigated the effects of fin pitch on multi-louvered flat tube HE using 20 types of HE having different fin pitches. More recently, P. Wais [25] performed a three-dimensional simulation using ANSYS software with fixed inlet air velocity and fin spacing to analyse the effect of louver inclination angle of a car radiator having circular tubes. The heat transfer strongly depends on the louver angle and the maximum value of the outlet air temperature reaches at 45º louver inclination angle.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the fact that they are the simplest and cheapest. However, the wake region behind the circular tube reduces the heat transfer on downstream fin region [13]. The optimum heat transfer rate can be obtained by varying the geometrical parameters of the tubes.…”
Section: Introductionmentioning
confidence: 99%